Evaluation of Protective Effects of Different Feeder Layers on Mouse Embryonic Stem Cells - AR Shams (Babol University of Medical Sciences, 2009)
BACKGROUND AND OBJECTIVE: Application of stem cells in medical research and treatment has made a new horizon to progress in many disorders. So finding methods for better isolation and culture and maintenance of stem cells (SC) has a specific importance. Aim of this research was to evaluate the protective effects of 3 different layers of mesenchymal stem cells (MSC), mouse embryonic fibroblast (MEF) and 3T3 on Sc for increasing the amounts of cells for transplantation and differentiation. METHODS: Blastocysts were obtained from 10 Balb/c pregnant mice. Collected embryos were put on 3 different feeder layers of mouse embryonic fibroblast (MEFs), Mesenchymal stem cells (MSC) and 3T3 cell line. Two or 3 days later, the zona pellucida was removed and after 5 days the inner cell mass (ICM) growth, was removed mechanically and changed to small multi-cellular clumps through trypsination. Then formed colonies were cultured on feeder layers. Finally the colonies were identified through staining with alkaline phosphates for their numbers and morphological characteristics.FINDINGS: From 29 embryos put on MEF layer all t of them (100%) was attached. From 32 embryos put on the MSC layer (64.5%) was attached. While the amount of attaching of 20 blastocysts to the 3T3 feeder layer was low and none of them reach to the growth stage of the inner cell mass. The amount of colonies formation during three passages on MEF feeder layer was more than MSC feeder layer. Data analysis demonstrated a significant difference (p<0.05) in percentage and time of hatching and time for living of blastocysts CONCLUSION: Considering these three feeder layers, MEF was better than MSC and both of them had priority to 3T3.